The relationship between intrinsic motivation and job engagement among Gen Y employees at National Heart Institute : work-life balance as moderating effect / Nor Diyana Rosli and Aliza Abu Hassim - Rosli, Nor Diyana; Abu Hassim, Aliza (Universiti Teknologi MARA, Shah Alam, 2017)
Job Engagement among Gen Y employees become an issue in today's world. This is due to the higher percentage of job hopping among Gen Y employees in which 65% of Gen Y employees work at their job less than two years. Besides that, there is a new gap about the relationship between Intrinsic Motivation among Gen Y employees towards Job Engagement. Hence, the paper shares two research objectives. The first objective is on the relationship between Intrinsic Motivation dimension (Job Autonomy, Competency, and Relatedness) and Job Engagement among Gen Y employees. Secondly, is the moderating effect of Work-life balance towards the relationship between Intrinsic Motivation and Job Engagement among Gen Y employees at the National Heart Institute (IJN). The unit analysis of this study is among Gen Y employees in the National Heart Institute (IJN). Data was conducted by using parametric analysis, which is the Pearson Correlation to determine first objective and PROCESS SPSS by Hayes was used to test moderator effect of moderating variable towards the relationship between Intrinsic Motivation and Job Engagement. Hence, the findings show that there is a relationship between Intrinsic Motivation (Job Autonomy, Competency, and Relatedness) and Job Engagement among Gen Y employees in IJN. The findings also show that there is moderator effect of Work-Life Balance towards the relationship between Intrinsic Motivation and Job Engagement. Thus, there is two recommendations for future research, firstly is to conduct the study with larger sample size and focus group is among Gen Y employees who are working in the public department agencies and ministry and secondly is conduct the study about technology as a moderator factor between Independent Variable and Dependent Variable.